Why do readers fail to notice word transpositions, omissions, and repetitions? A review of recent evidence and theory. - Kuan-Jung Huang; Staub, Adrian (Language & Linguistics Compass, 2021)
Most readers have had the experience of initially failing to notice an omission or repetition of a function word, or a transposition of two adjacent words. In the present article, we review recent research investigating this phenomenon. We emphasize that failure to notice such errors is of substantial theoretical interest, given what we have learned about how systematically and incrementally readers inspect and process text. We endorse the idea that a process of rational inference may play a critical role, while we cast doubt on the idea that failure to notice errors arises from parallel processing of multiple words. We review a number of recent studies from our own laboratory that have investigated the relationship between eye movements during reading and noticing, or failing to notice, an error. While the conclusions from these studies are broadly consistent with a rational inference account, we find that when readers fail to notice an error, their eye movements generally show no indication that the error was registered at all. On its surface, this finding may be viewed as inconsistent with the idea that the rational inference process that enables readers to overlook errors is genuinely post-perceptual. We suggest a mechanism by which eye movement control models could account for this finding.